Processing speed training increases the efficiency of attentional resource allocation in young adults - Burge, Wesley K.; Ross, Lesley A.; Amthor, Frank R.; Mitchell, William G.; Zotov, Alexander; Visscher, Kristina M. (Frontiers in Human Neuroscience, 2013)
Cognitive training has been shown to improve performance on a range of tasks. However, the mechanisms underlying these improvements are still unclear. Given the wide range of transfer effects, it is likely that these effects are due to a factor common to a wide range of tasks. One such factor is a participant's efficiency in allocating limited cognitive resources. The impact of a cognitive training program, Processing Speed Training (PST), on the allocation of resources to a set of visual tasks was measured using pupillometry in 10 young adults as compared to a control group of a 10 young adults (n = 20). PST is a well-studied computerized training program that involves identifying simultaneously presented central and peripheral stimuli. As training progresses, the task becomes increasingly more difficult, by including peripheral distracting stimuli and decreasing the duration of stimulus presentation. Analysis of baseline data confirmed that pupil diameter reflected cognitive effort. After training, participants randomized to PST used fewer attentional resources to perform complex visual tasks as compared to the control group. These pupil diameter data indicated that PST appears to increase the efficiency of attentional resource allocation. Increases in cognitive efficiency have been hypothesized to underlie improvements following experience with action video games, and improved cognitive efficiency has been hypothesized to underlie the benefits of PST in older adults. These data reveal that these training schemes may share a common underlying mechanism of increasing cognitive efficiency in younger adults.